The aplication of Chabi (charming dustbin) and Takakura basket as effort to increase environment indefferent for elementary school children - Rudi Setiawan; Rio Febrianto Arifendi (JPBI (Jurnal Pendidikan Biologi Indonesia), 2016)
This research was a action research. This research had conducted in two cycles, each cycle consists of planning, implementing, observing, and reflecting. The data used was qualitative data on field and supported by any quantitative data like observation sheet instruments and angket. The results of this research are 86% students excited to waste any garbage on its place, 88% students have common to separate any garbage based on its kind, and 92% students showed care on environment. This result of research have conclusion like 1) The students excited to waste any garbage by chabi and takakura basket.2)The students have common to separate organic and anorganic garbages. 3) The student have good care on environment health by using chabi and takakura basket on waste any garbage.